Matching Instruction with Modality-Specific Learning Style: Effects on Immediate Recall and Working Memory Performance - Karoline Aslaksen; Håvard Lorås (Education Sciences, 2019)
A well-known hypothesis in education and amongst the general public is that matching instructional method with an individual’s modality-specific learning style improves learning and cognitive performance. Several critical reviews in the past decade, however, have shown that the hypothesis has not been properly evaluated with appropriate methodology. Furthermore, the association between learning style and other cognitive abilities such as working memory has not been examined. Thus, the aim of the current study was to examine the association between modality-specific learning style, immediate recall, and working memory performance. University students with visual or auditory learning styles were randomly assigned to one of two instructional methods and then given a multiple-choice recall test. In addition, the participants completed working memory tasks with visual or auditory presentation. The results failed to support the matching hypothesis or any association between modality-specific learning style and working memory.